2018
DOI: 10.1080/15563650.2018.1479527
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-fibrotic treatment in a rodent model of acute lung injury induced by sulfur dioxide

Abstract: To enable an accurate extrapolation of animal derived data to humans, a detailed understanding of the underlying mechanisms of the injury, and potential treatment options, is needed. The findings of the present study suggest that treatments with the capability to reduce both AHR, the inflammatory response, and fibrosis are needed to achieve a comprehensive mitigation of the acute lung injury caused by SO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…These changes are consistent with the pathological process of acute lung injury and once again confirmed that sepsis can be caused by acute lung injury. Endogenous sulfur dioxide may play a protective role in lung injury as found in previous studies [19]. In this study, after the endogenous SO 2 donor Na 2 SO 3 /NaHSO 3 was given, the lung tissue structure, lung capillary permeability, and the obvious thickening of the alveolar compartment were all improved; the wet weight/ dry weight ratio of lung tissue and the histology of lung injury was improved.…”
Section: Discussionsupporting
confidence: 76%
“…These changes are consistent with the pathological process of acute lung injury and once again confirmed that sepsis can be caused by acute lung injury. Endogenous sulfur dioxide may play a protective role in lung injury as found in previous studies [19]. In this study, after the endogenous SO 2 donor Na 2 SO 3 /NaHSO 3 was given, the lung tissue structure, lung capillary permeability, and the obvious thickening of the alveolar compartment were all improved; the wet weight/ dry weight ratio of lung tissue and the histology of lung injury was improved.…”
Section: Discussionsupporting
confidence: 76%
“…Wigenstam et al. (2018) also reported that rats exposed to SO 2 showed labored breathing and decreased bodyweight.…”
Section: Discussionmentioning
confidence: 95%
“…The body weight of male mice was significantly reduced by SO 2 . Wigenstam et al (2018) also reported that rats exposed to SO 2 showed labored breathing and decreased bodyweight.…”
Section: Effect Of Ebn On the Immunological Function Of Mice With Lun...mentioning
confidence: 92%
“…Wigenstam et al conducted a study in 2018 and observed that, with some mucosal damage occurring to a lesser degree, there was no pulmonary edema. In addition, the development of fibrosis was inhibited compared to the control group, as revealed by the histopathological examination of the tissues collected from the subjects treated with three doses of 200 mg/kg intraperitoneal pirfenidone after inducing iatrogenic pulmonary damage by sulfur dioxide.…”
Section: Discussionmentioning
confidence: 99%